2019
DOI: 10.3390/toxins11110635
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Trimethylamine-N-Oxide in Chronic Kidney Disease: Contribution of Decreased Glomerular Filtration Rate

Abstract: Gut microbiota-dependent Trimethylamine-N-oxide (TMAO) has been reported to be strongly linked to renal function and to increased cardiovascular events in the general population and in Chronic Kidney Disease (CKD) patients. Considering the lack of data assessing renal handling of TMAO, we conducted this study to explore renal excretion and mechanisms of accumulation of TMAO during CKD. We prospectively measured glomerular filtration rate (mGFR) with gold standard methods and plasma concentrations of trimethyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 31 publications
(51 reference statements)
8
65
1
Order By: Relevance
“…In the present study, our results are consistent with previous reported data in CKD adults [31,32], showing that TMAO is increased in CKD with a weak inverse correlation (r = −0.283) between plasma TMAO level and eGFR. Our results are also in agreement with a previous report in CKD adults showing urinary excretion is a dominant route for TMAO elimination with a steady fractional excretion of TMAO, regardless of the CKD stages [32]. However, we observed lower urinary TMAO levels in children with CKD stage G2−G4 than those with stage G1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, our results are consistent with previous reported data in CKD adults [31,32], showing that TMAO is increased in CKD with a weak inverse correlation (r = −0.283) between plasma TMAO level and eGFR. Our results are also in agreement with a previous report in CKD adults showing urinary excretion is a dominant route for TMAO elimination with a steady fractional excretion of TMAO, regardless of the CKD stages [32]. However, we observed lower urinary TMAO levels in children with CKD stage G2−G4 than those with stage G1.…”
Section: Discussionsupporting
confidence: 93%
“…Gut microbiota-derived metabolites TMAO, TMA, and DMA from dietary methylamines have recently gained much attention due to their high association with CV risk [8][9][10]29,30]. In the present study, our results are consistent with previous reported data in CKD adults [31,32], showing that TMAO is increased in CKD with a weak inverse correlation (r = −0.283) between plasma TMAO level and eGFR. Our results are also in agreement with a previous report in CKD adults showing urinary excretion is a dominant route for TMAO elimination with a steady fractional excretion of TMAO, regardless of the CKD stages [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2 Accumulating evidence has suggested that TMAO upregulation is implicated in cardiovascular disease 3 and chronic kidney disorders, 4 and is correlated with a high risk of the occurrence of ischemic events. 5 Previous studies showed that TMAO accumulates in chronic kidney disease patients, 6,7 and its elevation is associated with an increased risk of mortality. 7 In particular, a high level of TMAO has been found in hemodialysis patients at the peak midweek predialysis.…”
Section: Introductionmentioning
confidence: 99%
“…5 Previous studies showed that TMAO accumulates in chronic kidney disease patients, 6,7 and its elevation is associated with an increased risk of mortality. 7 In particular, a high level of TMAO has been found in hemodialysis patients at the peak midweek predialysis. 8 A wide range of mass spectrometry (MS)-based analytical methods coupled with liquid chromatography (LC) or gas chromatography have been developed for the measurement of TMAO in biological samples.…”
Section: Introductionmentioning
confidence: 99%